Educating students with FASD: linking policy, research and practice. Issue 1 (19th November 2014) - Millar, Julie A.; Thompson, Janet; Schwab, Dorothy; Hanlon‐Dearman, Ana; Goodman, Deborah; Koren, Gal; Masotti, Paul
Abstract : Fetal alcohol spectrum disorder (FASD) is a prevalent neurodevelopmental disability with significant implications for learning and behaviour. International research suggests that the prevalence of FASD in school‐aged children is 2.3–6.3%. In this paper, we address the questions: (1) what is FASD; (2) what is the prevalence of FASD in schools; (3) what is the impact of FASD; and (4) why develop special FASD education strategies and programmes? We summarise the 18‐year history of Winnipeg School Division's development of its FASD Programme of services, describe the specialised FASD classrooms and then present the results from a consensus‐generating workshop comprised of 36 FASD education professionals, with over 209 years of collective FASD education programme experience, who were asked to identify and reach consensus on best strategies and lessons learned in FASD education programmes. We then suggest that effectively educating children with FASD is critical to get right if positive educational outcomes are to be realised.